Family narratives in Tor-tor performances as a medium for building collective memory and ethnic identity of Mandailing, Indonesia - Novita, Elmi (Universitas Dian Nuswantoro, 2025)
This research explains the family narrative in tor-tor performances as a medium of building collective memory, identity and communicating Mandailing cultural values. Research methods through narrative examination, observation of tor-tor performances, and narrative interviews. The results showed that family narratives and performance forms support each other in building collective memory, identity and communicating Mandailing cultural values. Family narratives have sequential structures and themes about the journey of family life. Meanwhile, the tor-tor form of performance supports the presence of diverse family narratives and collaborations involving the active role of families, singers, dancers and audiences